Efektivitas Kepemimpinan Dalam Meningkatkan Transparansi dan Akuntabilitas Di Kantor Wali Nagari Sungai Buluah Utara - Anisa Saputri; Annisah Fatin; Azizah Jumaita Ayu; Fatimah Azzahra; Abdul Hamid Gusri; Syamsir Saili (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Leadership plays a very important role in creating a transparent and accountable government, especially at the local government level such as the village head. Leadership effectiveness is a key factor in ensuring that every policy and work program can run well and in accordance with the principles of transparency and accountability. This study aims to determine the effectiveness of leadership in increasing transparency and accountability at the Sungai Buluah Utara village head office. The research method used is a qualitative approach to see the condition of scientific objects with data collection techniques, namely observation, interviews and documentation. The object of this study is the Sungai Buluah Utara Village Head Office, Batang Anai District. The results of the study showed . This finding indicates that the leadership of the Sungai Buluah Utara Village Head effectively encourages transparency and accountability in the implementation of government and public services. The commitment of the leader, which is reflected in the action of opening access to information, building two-way communication with the community, and increasing the capacity of the apparatus, is in line with the principles of good governance and relevant leadership theories. The application of a humanistic leadership style and orientation towards excellent service contributes significantly to increasing public trust. Although the current implementation is going well, the study also identified potential challenges for the future, including maintaining consistency, adapting technology, maintaining community participation, potential internal resistance, resource constraints, and measuring impact.